Emotional Intelligence Correlation with Self Efficacy in Adolescent - Endang Mei Yunalia; Arif Nurma Etika (Media Keperawatan Indonesia, 2020)
Adolescence is a transitional stage from the stage of the child to the stage of adult growth and development, wherein this transition there are many changes physical or biological, cognitive, and emotional aspects. As a result of emotional changes in adolescents usually when adolescents are confronted with stressors can cause negative feelings to arise, where negative feelings experienced by adolescents are related to one's belief in one's ability to cope with stressors or so-called self-efficacy. The purpose of this study was to determine the correlation between emotional intelligence with self-efficacy in adolescents. This research is a correlational analytic study through the cross-sectional approach. The population in this study was all students in the Faculty of Health Sciences, Kadiri University. Samples of 191 respondents were selected using a simple random sampling technique. The statistical test of research data uses the Spearman Ranks Test. Statistical test results show p = 0,000 (p-value <0.05), means that there is a correlation between emotional intelligence and self-efficacy in adolescents. The results of this study can be used as a basis for providing intervention for adolescents to further maximize the development of emotional intelligence and achievement of self-efficacy in adolescents so adolescents can manage negative emotions and have confidence in abilities from themselves, so adolescents can overcome negative emotions that arise due to the stressors.